2018
DOI: 10.17681/hsp.380847
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelik Öğrencilerinin Empati Düzeyleri Ve Problem Çözme Becerileri

Abstract: ÖZ Bu çalışma, hemşirelik öğrencilerinin empatik eğilim düzeylerini ve problem çözme becerilerini değerlendirmek amacıyla yapılmıştır. Yöntem: Çalışmanın evrenini 2017-2018 eğitim öğretim yılında bir üniversitede lisans eğitimi gören hemşirelik öğrencileri oluşturmuştur. Herhangi bir örnekleme yöntemine başvurulmayıp çalışmaya katılmayı kabul eden bütün öğrenciler çalışma kapsamına alınmıştır. Çalışmaya katılmayı kabul eden öğrencilere tanımlayıcı özellikleri içeren form, Empatik Eğilim Ölçeği ve Problem Çözme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
1
2
0
3
Order By: Relevance
“…The average of total EQ points of the students taking part in the research, who willingly chose their profession, was found to be higher according to that of those who did not, and there was a significant difference in between. The study by Ustundag et al where similar results to this research were obtained, determined that, the average of total Empathy Tendency Scale points of participants who freely chose their profession was higher when compared to that of those who did not and that there was a significant difference in between [27]. Researches with different results also exist in literature; for instance, the research by Turan et al carried out on a group of 290 nursing students, showed an average of total Empathic Skills Scale points of students who freely chose their profession was found lower than that of those who did not, and no significant difference was found [20].…”
Section: Discussionsupporting
confidence: 82%
“…The average of total EQ points of the students taking part in the research, who willingly chose their profession, was found to be higher according to that of those who did not, and there was a significant difference in between. The study by Ustundag et al where similar results to this research were obtained, determined that, the average of total Empathy Tendency Scale points of participants who freely chose their profession was higher when compared to that of those who did not and that there was a significant difference in between [27]. Researches with different results also exist in literature; for instance, the research by Turan et al carried out on a group of 290 nursing students, showed an average of total Empathic Skills Scale points of students who freely chose their profession was found lower than that of those who did not, and no significant difference was found [20].…”
Section: Discussionsupporting
confidence: 82%
“…It was reported that first-year nursing students experienced high levels of anxiety on the first day of their clinical trial and their state anxiety levels were high; however, their state anxiety levels had decreased by the end of the trial. 2,6,20 reported that the anxiety of students who practiced with mentors decreased significantly and majority developed their clinical performance. Some of studies have found that the anxiety experienced by students decreased significantly in their clinical practice after working with mentors.…”
Section: Resultsmentioning
confidence: 99%
“…1 At the end of this educational process, students are expected to help patients solve their health problems by using knowledge, attitudes, skills and scientific problem solving methods. 2 While trying to meet these expectations, the student may experience frustration, regret, stress, and disappointment, as well as positive experiences. Sources of stress among nursing students can be varied: theoretical education based on memorization, inadequate Student-teacher relationship in practice environments and lack of professional knowledge and skills in clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Araştırma bulgularının aksine, Üstündağ ve ark. 'nın (2018) çalışmasında hemşirelik öğrencilerinin empatik beceri eğitimi alma durumları ile empatik eğilim düzeyleri arasında fark saptanmamıştır (32). Gazo ve ark.…”
Section: Dokuz Eylül üNiversitesi Hemşirelik Fakültesi Elektronik Dergisiunclassified